Avaliação comparativa da posição condilar pela Tomografia Computadorizada de feixe Cônico (TCFC) nas más oclusões de Classe I e Classe II esquelética - Carinhena, Caio Fabre (2010)
This study aimed to evaluate anteroposterior of the condyle through the Cone Beam Computed Tomography (CBCT) in a group of 24 patients 12 with Class I malocclusion (Group I) and 12 with Class II malocclusion, skeletal (Group II), whitout orthodontic treatment. The images are from the Sao Paulo city´s Department of orthodontic documentation files – UNICID and from a privace office´s file. Measurements were taken through a software nemotec Dental Studio 8.7, to assess the posterior and superior spaces of de condyle in relation to the glenoid fossa. The measurements obtained were used to set the condylar position in Groups I and II. There was no absolute concentricity of any of the condyle in both groups evaluated. The group with bad occlusion of Class II demonstrated bigger posterior space between condyle and articular fossa, resultin on more anterior condyles in this group.